(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم حساب طاقة السويات وكذلك حساب طاقة السويات الفرعية لنواة الكالسيوم , مما سمح لنا بحساب قيمة انزياح السويات الطاقية نحو الأعلى ونحو الأسفل , وبالتالي استطعنا حساب طاقة انقسام السبين – مدار في الحالتين الطاقيتين , وكذلك وأصبح لدينا تصور حول مخطط طيف طاقة نواة الكالسيوم , وذلك في إطار نموذج النيكليون المفرد مع الاشارة أنه تم استخدام جهد نووي يحوي تأثيرات مركزية وتنسورية عند كتابة التابع الهاملتوني لمعادلة ديراك. Energy levels were calculated, as well as calculation the energy sublevels of the nucleus of calcium , which allowed us to calculate the value of the drift energy levels up and down and thus we can calculate the energy splitting of spin-orbit in both cases over as well and we have a vision for the energy spectrum of the core scheme of calcium in the framework of a single model nucleon. We draw your attention that have used nuclear potential that contains the effects of central and Tensor in Hamiltonian of Dirac equation.